Maternal pre‐pregnancy underweight as a risk factor for the offspring: Survey of Neonates in Pomerania. (10th December 2020) - Domanski, Grzegorz; Lange, Anja Erika; Ittermann, Till; Fallenberg, Jonas; Allenberg, Heike; Zygmunt, Marek; Heckmann, Matthias
Abstract: Aim: The aim was to investigate socio‐economic risk factors for maternal underweight before pregnancy and then associations of underweight with neonatal outcomes. Methods: Data of 3401 mother‐child dyads from the population‐based birth cohort Survey of Neonates in Pomerania (SNiP) were analysed. Results: Bivariate analysis showed that underweighted mothers were younger, smoked more often, had a lower equivalent income and lower socio‐economic status (employment status and/or educational level) compared to women with normal weight. The final prediction model revealed that only younger maternal age (OR = 0.93; 95%‐CI = 0.90‐0.97) and maternal smoking during pregnancy (OR = 2.52; 95%‐CI = 1.74‐3.66) were associated with underweight. Compared to women with normal pre‐pregnancy BMI, underweight women had an increased chance of premature labour (OR = 1.73; 95% CI: 1.29‐2.31) and a reduced placental weight. The offspring of underweight women had an increased risk of late preterm birth (OR = 1.82; 95% CI: 1.21‐2.74) and birthweight < 2500 g (OR = 1.91; 95% CI: 1.23‐2.95). Conclusion: Smoking during pregnancy and a younger age were identified as risk factors for maternal pre‐pregnancy underweight which then was associated with late preterm birth and low birthweight.